The Influence of Work Professionalism, Transformational Leadership, and Organizational Commitment on the Performance of Regional Development Planning, Research and Development Agency Employees Hulu Sungai Utara Regency - Kadir, Abdul; Pateriah; Jayen, Fredy; Amrulloh, Rifqi (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2024)
This study aims to analyze the influence of professionalism, transformational leadership, and organizational commitment on the performance of employees at the Hulu Sungai Utara Regency Regional Development Planning, Research, and Development Agency. The research will use a descriptive quantitative approach with a survey. Questionnaires will be distributed to all employees at the agency, totaling 34 people. Saturated sampling will be employed as the sample, as the population is less than 100. Multiple regression analysis will be conducted to test the data and measure the influence of the independent variables on the dependent variable. The results of the analysis demonstrate that professionalism, transformational leadership, and organizational commitment have both simultaneous and partial effects on the performance of employees at the agency.